2009
DOI: 10.1038/oby.2009.184
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Weight Loss With Pramlintide/Metreleptin: An Integrated Neurohormonal Approach to Obesity Pharmacotherapy

Abstract: The neurohormonal control of body weight involves a complex interplay between long‐term adiposity signals (e.g., leptin), and short‐term satiation signals (e.g., amylin). In diet‐induced obese (DIO) rodents, amylin/leptin combination treatment led to marked, synergistic, fat‐specific weight loss. To evaluate the weight‐lowering effect of combined amylin/leptin agonism (with pramlintide/metreleptin) in human obesity, a 24‐week, randomized, double‐blind, active‐drug‐controlled, proof‐of‐concept study was conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
196
0
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 288 publications
(207 citation statements)
references
References 36 publications
5
196
0
6
Order By: Relevance
“…The physiological effects of amylin receptor agonism include decreased food intake [4] and reduction of postprandial glucagon release in a glucose-dependent manner [5]. Moreover, it has been proposed that a combination of amylin and leptin may be more effective than leptin or amylin alone for treatment of obesity in both animals [2] and humans [5]. Adiponectin, the most abundant adipokine in circulation, is synthesised and secreted by adipose tissue [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The physiological effects of amylin receptor agonism include decreased food intake [4] and reduction of postprandial glucagon release in a glucose-dependent manner [5]. Moreover, it has been proposed that a combination of amylin and leptin may be more effective than leptin or amylin alone for treatment of obesity in both animals [2] and humans [5]. Adiponectin, the most abundant adipokine in circulation, is synthesised and secreted by adipose tissue [6].…”
Section: Introductionmentioning
confidence: 99%
“…Amylin is a 37-amino-acid peptide hormone that is co-secreted with insulin from pancreatic beta cells [4]. The physiological effects of amylin receptor agonism include decreased food intake [4] and reduction of postprandial glucagon release in a glucose-dependent manner [5]. Moreover, it has been proposed that a combination of amylin and leptin may be more effective than leptin or amylin alone for treatment of obesity in both animals [2] and humans [5].…”
Section: Introductionmentioning
confidence: 99%
“…There has also been interest in combining leptin with other therapeutic drugs to induce weight loss. Amylin and Takeda were pursuing the combination of pramlintide and metreleptin as an anti-obesity therapy, and the combination showed promising results in early clinical trials (17). However, in 2011, phase II clinical trials were halted and the program was discontinued after patients reportedly developed antibodies to metreleptin.…”
Section: Discussionmentioning
confidence: 99%
“…45 The combination of leptin with pramlintide, however, produced additive weight loss in a 6-month clinical trial that may offer promise for the future. 46 Clinical trials have shown weight-loss results with leptin alone to be disappointing, but a 6-month trial combining leptin with pramlintide produced an additive weight loss that may offer promise for the future.…”
Section: Pramlintide and Leptinmentioning
confidence: 99%